Comparison of actual performance in humidification among different high-flow nasal cannula devices: a bench study - Ni, Zhong; Zhou, Yuyan; Tang, Na; Yu, He; Liang, Zongan (Frontiers in Medicine, 2023)
Background The physiological effects of HFNC devices are closely related to temperature and humidity. HFNC devices from different manufacturers may have varied performances. It is unclear whether there are differences in the humidification performance of different HFNC devices and the degree of differences. Methods Four integrated HFNC devices (AIRVO 2, Fisher & Paykel Healthcare, Auckland, New Zealand; TNI softFlow 50, TNI Medical AG, Würzburg, Germany; HUMID-BH, RESPIRACARE, Shenyang, China; OH-70C, Micomme, Hunan, China) and a ventilator with an HFNC module (bellavista 1000, Imtmedical, Buchs, Switzerland) were evaluated using their matching circuits. The dew point temperature was set at 31, 34, and 37°C (set-DP). In MR850, it was set to non-invasive mode (34°C/−3°C) and invasive mode (40°C/−3°C), respectively. At each level of set-DP, the flow was set from 20 L/min up to its maximum set limit at a gradient of 5 L/min or 10 L/min. After stabilization, the dew point temperature, temperature, relative humidity, and flow rate of the delivered gas from the cannulas were recorded. Results There were significant differences in actual-DP among these devices at any set-DP (p < 0.001). The actual-DP of OH-70C and TNI softFlow 50 was lower than set-DP, and the difference between the actual-DP and the set-DP of these two devices increased with the increase of set-DP. AIRVO 2, bellavista 1000 (MR850), and HUMID-BH can provide the nominal humidity at 37°C. The actual-DP increased with the increase of set-flow under each set-DP in AIRVO 2, TNI softFlow 50 and bellavista 1000 (MR850), but decreased when the set-flow was greater than 60 L/min. The actual-T of the delivered gas was higher than actual-DP in all devices and was higher than set-DP in AIRVO 2 and HUMID-BH. Conclusion Set-flow, set-DP, and types of devices will affect the actual temperature and humidity of the delivered gas. AIRVO 2, bellavista 1000 (MR850), and HUMID-BH can provide the nominal humidity at 37°C and may be more suitable for tracheotomy patients. The flow rate over 60 L/min should be set with caution.